529 Gallstone Disease and the Risk of Cardiovascular Disease – a Mendelian Randomisation Study. (19th August 2022) - Fairfield, C; Drake, T; Pius, R; Bretherick, A; Campbell, A; Clark, D; Fallowfield, J; Hayward, C; Henderson, N; Iakovliev, A; Joshi, P; Mills, N; et al.
Abstract: Aim: Gallstones present frequently to surgical units and share risk factors with cardiovascular disease (CVD). Little is known about long-term CVD risk or the presence of any causal relationship. The aim of this study is to assess long-term CVD risk in gallstone-carriers and assess causality through Mendelian randomisation (MR). Method: 458, 968 UK Biobank (UKB) participants free from baseline CVD were assessed. Cox regression adjusting for gallstones, age, sex, diabetes, smoking, anthropometric data, serum lipids, exercise and diet was conducted to assess CVD risk after 10 years in gallstone-carriers compared to controls. Two-sample MR was conducted with gallstone-susceptibility variants from the UKB and CVD-susceptibility variants from CardiogramPlusC4D in inverse-variance-weighted meta-analysis. Multivariable MR adjusting for lipid-, smoking- and diabetes-susceptibility variants was undertaken. Results: Risk of CVD was higher in gallstone-carriers than controls (2, 579/32, 528 [7.1%] versus 23, 249/426, 082 [5.5%]; adjusted-hazard-ratio 1.48, 95%CI 1.42–1.54). MR demonstrated the opposite, with protective impact of genetic liability to gallstones on CVD (odds-ratio 0.94, 0.89–0.997). Leave-one-out analysis of each variant revealed strongly protective impact of D19H ABCG8 mutation which lowers serum lipids via biliary efflux. Multivariable MR revealed no significant association (odds-ratio 1.02, 0.93–1.11). Univariable MR after excluding all lipid-lowering variants revealed no association. Conclusions: Gallstone-carriers experience elevated CVD risk partly explained by shared risk factors. MR demonstrated a negative relationship between genetic liability to gallstones and CVD. This was explained by lipid-lowering gallstone-susceptibility variants. Genetic liability to gallstones reduces CVD risk through lowering serum lipids. Gallstones remain a sentinel presentation of CVD risk due to shared environmental but not genetic exposures.